(untitled) (Medico Legal Update, 2023)
Road traffic injuries are a major public health problem and a leading cause of death and injury around the world. Each year nearly 1.2 million people die as a result of road crashes, and millions more are injured or disabled. According to the National Highway Traffic Safety Administration (NHTSA), motorcycle riders are 26 times more likely to die in a traffic collision than passenger vehicle occupants, and 5 times more likely to be injured. In a study conducted by NHTSA on 104,472 motorcyclists injured in traffic crashes, 15 percent of helmeted and 21 percent of unhelmet riders suffered TBI. A helmet aims to reduce the risk of serious head and brain injuries by reducing the impact of a force or collision to the head. A helmet works by, reducing the deceleration of the skull, spreads the forces of the impact over a greater surface area and by preventing direct contact between the skull and the impacting object. Present study was carried out in Mahadevappa Rampure Medical College, Kalaburagi with the aim to know cause of death in deaths due to bike accidents autopsied at Mahadevappa Rampure Medical College, Kalaburagi between 2011 to 2016(6-year retrospective study). Results of the study shows that out of 100 cases, in 65 cases cause of death was head injury and in 35 cases it was hemorrhagic shock, septicemia, multi organ failure and others. In 48% of cases injuries were seen in thoracic region and in 40% of cases abdominal injuries. Whereas in 34 cases except intracranial hemorrhage no other injuries were seen on the body. The present study shows that maximum deaths can be prevented by wearing a proper protective helmet.